The role of micro-organisms in the production of semiochemicals in the interdigital secretion of the bontebok, Damaliscus pygargus pygargus - Scott, Gary Terri (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2004.